تصميم ونمذجة نظام تحويل طاقة ريحي في منطقة قطينة والتحكم به بهدف ربطه مع الشبكة الكهربائية السورية - ياخور, يوسف; شاهين, حسام; علي, زينة أديب (Latakia University Journal -Engineering Sciences Series, 2014)
تعد منطقة قطينة في محافظة حمص من أكثر المناطق في سورية ملائمةً لإنشاء نظام تحويل طاقة ريحي. يمكن ربط هذا النظام مع الشبكة الكهربائية السورية بدون تكاليف كبيرة نظراً لقرب المنطقة من الشبكة. لكن تغير سرعة الرياح، الدائم وغير المستقر، يؤدي إلى ظهور جهود مختلفة في التردد و المطال على خرج النظام غير مطابقة لجهد وتردد الشبكة الكهربائية السورية مما يعيق عملية الربط. يهدف هذا البحث إلى تصميم نظام تحويل طاقة ريحي ملائم لمنطقة قطينة والتحكم به بحيث نحصل دائماً على جهد وتردد ثابتين ومطابقين لجهد وتردد الشبكة الكهربائية السورية لتسهيل عملية ربطه مع الشبكة. وذلك عند أي سرعة رياح على دخل النظام الريحي ومن أجل أي حمولة على خرجه. تم اختيار العنفة الملائمة والمولد الملائم للمنطقة اعتماداً على بارامترات تابع احتمالي رياضي، يسمى تابع وايبل (Weibull Function). بعد ذلك تم تصميم نظام التحكم المناسب لمطابقة خرج النظام الريحي من جهد وتردد مع جهد وتردد الشبكة الكهربائية السورية. حيث تم التحكم بالمقطع الرافع - الخافض باستخدام متحكم تناسبي تكاملي (Proportional Integral) بحيث نحصل دائماً على جهد خرج مستمر ثابت مقداره . أما عملية التحكم بالقالبة فقد تمت باستخدام حلقتي ، حلقة خارجية للتحكم بالجهد وحلقة داخلية للتحكم بالتيار. وذلك من أجل الحصول على جهد جيبي ثلاثي الطور قيمته الفعالة الطورية (220V) وتردده (50 Hz). للتحقق من صحة وصلاحية وفعالية النظام المقترح، تمت نمذجته ببرنامج MATLAB ومحاكاة عمله. وقد أظهرت نتائج المحاكاة إمكانية الحصول على جهد ذو مطال وتردد ثابتين لا يتغيران بتغير سرعة الرياح أو الحمولة . Kouttina is one of the most proper areas in Syria for building wind energy conversion system. This system could be coupled with Syrian electrical grid without expensive cost because of nearing from the grid. But, the permanent changes of wind speed with no stable mode, cause different amplitude and frequency voltages differ from Syrian electrical grid amplitude and frequency. The goal of this research is to design proper wind energy conversion system for Kouttina area and control it, therefore, we always obtain constant amplitude and frequency voltages equal to those of Syrian electrical grid for any wind speed and load. The proper wind turbine with its generator was chosen depending on parameters of probability mathematic function, called Wiebull Function. After that, the proper control system was designed for equaling the amplitude and frequency of wind energy conversion system output with those of Syrian electrical grid. The buck -boost converter was controlled by proportional integral (PI) controller to always have DC output voltage equal to (622V). While the inverter controller was achieved by using two PI control loops, the outer loop for voltage control and the inner loop for current control. Though, three phase voltage with RMS phaser value of (220V) and frequency value of (50Hz) is achieved. To validated the correctness and effectiveness of the proposed system, it was modeled using MATLAB program. The results showed the system ability of obtaining voltage with constant amplitude and frequency and this values do not change with wind speed or load changes.